With Respect to Prejudice - Maitra, Begum (Journal of analytical psychology, 2019)
The basic assumptions of psychotherapy must necessarily reflect the cultural orientations and dilemmas of the western societies, and historical periods, in which these originated. This paper considers how the racialised biases of that period, namely, the era of European domination built upon the conquest, colonisation and enslavement of non-European peoples, may linger in psychotherapeutic training and practice today. This not only limits the potential usefulness of the discipline in the multicultural populations of the west, but also risks it being read as covert neo-colonialism in the ‘non-west’. In a world that ever more clearly demonstrates the human costs of prejudice psychotherapists in general, and Jungians in particular, might wish to consider how, wittingly or otherwise, they maintain prejudiced ways of thinking. This paper examines material from the author's professional and personal experience, using literature that lies outside the specifically Jungian canon, to expose how such bias might work.